(untitled) (Bangladesh Journal of Nuclear Medicine, 2018)
Cutaneous and subcutaneous metastases from internal malignancies are rare. The reported incidence of subcutaneous metastasis is 5.3% and cutaneous metastasis account for 0.7% and 9% of all metastases. Here we reported two cases of cutaneous metastasis, one from gall bladder cancer and other from breast cancer. Among all internal malignancies the incidence of cutaneous metastasis in breast cancer is highest whereas in gall bladder cancer is rare. Detection of cutaneous or subcutaneous metastasis determines the staging, prognosis and management strategy of the disease. 18F FDG PET- CT (18 Fluorine fluorodeoxyglucose positron emission tomography computerized tomography) scan has been reported to play a potential role in the identification of cutaneous or subcutaneas metastasis. These metastases were detected on whole body 18F FDG PET-CT scan during restaging of the disease. The lesions were FDG avid and biopsy proven metastasis. Intense FDG avidity with SUV max 10.5 was revealed in nodular lesion in abdominal wall from gall bladder cancer. The nodular lesion in gluteal region in a patient with breast cancer had low avidity with SUV max 3.8 later evaluated as cutaneous metastasis. Here the cases are reported to emphasize the PET-CT imaging as a potentially used one-stop-shop imaging modality in patients with cutaneous or subcutaneous metastases from internal malignancies. PET-CT imaging can reliably identify hypermetabolic cutaneous metastasis and can help not only to restage the disease but also to guide new therapeutic strategies. Bangladesh J. Nuclear Med. 20(1): 56-58, January 2017